Implementasi Konsep Idiom Surabaya “Karepe Dewe” pada Interior Pusat Komunitas Musik Indie di Surabaya - Edwin Edwin; Ronald Hasudungan Irianto Sitindjak; Jean Francois Poillot (Intra, 2017)
Music is a part that can’t be separated from everyday human life’s. In Indonesia itself, the music industry is one of the sectors of the creative economy with the greatest revenue. The music industry in Indonesia is divided into two, namely major label and one of them which is indie label whose musicians try to produce and marketing their music independently. With this self-supporting principle, then there are many indie music community in Surabaya city with the purpose of helping each other. Many indie musicians have great potential but have facility constraints and are less well known to the public. Indie music community center in Surabaya is a place for indie music community who want to work and develop their ability in music to a better level. In accordance with the concept of KAWE which means "karepe dewe", then the interior design is trying to create facilities that fulfill the indie music community as well as introduce it to the public more clearly and directed.